STRUCUTURAL AND GEOMECHANICAL ANALYSIS TO PREDICT NATURALLY FRACTURE CARBONATE RESERVOIR CAHARACTERIZATION OF WHF FIELD, BANGGAI BASIN, INDONESIA - Armanda, Reza; Gunawan, Indra (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2021)
The WFH field has been in production since 2005 with reserves of 120 MMBO and has reached peak production of up to 4000 BOPD. The reservoir rock from this field is Miocene Bioclastic Limestone with an average matrix porosity of 8% and a water saturation of 13%. Based on the results of the core rock study and analysis of well production tests, the reservoir in the WFH field indicates the presence of natural fractures that control porosity and permeability so that a mechanical approach such as structural and geomechanical analysis is needed to get an understanding of characteristics and distribution of natural fractures that the resolution is under seismic resolution.Geological structure parameters are obtained from the sesimic interpretation of reservoir horizon and several faults then reconstructed to obtain the strain value from this field. Geomechanical properties such as the stress regime in the WFH field are obtained from theresults of stress analysis. The stress analysis shows that the WFH field is in a normal fault regime (Sv> SHmax> Shmin). Structural reconstrution analysis showed a vertical strain value is 18% and horizontal strain value is -17%. This value is obtained from the sum of the movement of reservoir in the thrust fault plane. The slope modeling of the simulated fracture ranges from 35 to 40 degrees which is identical to the natural fracture observations obtained from the log image interpretation. The intensity of fractures in the WFH field reservoir is in the area around the fault plane, especially in the bend area. In addition, the intensity of fractures that could potentially open is indicated by a large Slip Tendency value of 0.4. The incorporation of areas with high slip tendency and fracture instensity resulted in an open natural fracture zone in this reservoir trending NW-SE which is associated with factoring faults that are identical to the trend of the WFH field structure.Modeling from this subsurface data is expected to be able to build a reliable geological and geomechanical structure model to provide the best recommendations for the placement of further wells and as an analogy in reducing the risk of exploration in a similar play